Association between obesity indexes and chronic kidney disease risk: a double-cohort prospective study in the Binhai and UK Biobank - Suhua Gao; Suhua Gao; Yixi Liu; Yixi Liu; Yixi Liu; Hongyan Liu; Hongyan Liu; Yao Lin; Yao Lin; Pufei Bai; Pufei Bai; Fang Hou; et al. (Frontiers in Endocrinology)
IntroductionThe prevalence of overweight and obesity has increased worldwide, leading to growing concern regarding the impact of visceral adipose deposition on renal function. The aim of this study was to evaluate the predictive value of 10 obesity indexes for the risk of chronic kidney disease (CKD) in both Chinese populations and Western.MethodsThe Tianjin Chronic Kidney Disease Study (Binhai, primary cohort) included 126,109 participants, while 358,918 adults from the U.K. Biobank (UKB, replication cohort) were included. Cox proportional hazard and restricted cubic spline models were used to assess the relationships between obesity indexes and the risk of CKD.ResultsDuring a median follow-up of 35 months in the Binhai cohort, 14,435 CKD cases were identified, while 358,918 CKD cases were observed in the U.K. Biobank cohort during 161 months of follow-up. The risk of CKD increased with increasing quartile levels of the Chinese Visceral Adiposity Index (CVAI) (P for trend < 0.001). CVAI was associated with increased CKD risk (hazard ratio in comparing the highest to the lowest quintile = 1.22 [95% CI 1.16-1.30]) and its predictive ability was the highest among the 10 obesity indexes, with an AUC value of 0.588 (0.581-0.594) in the female subgroup of the Binhai cohort. All of the obesity indexes were negatively correlated with estimated glomerular filtration rate (eGFR).DiscussionFindings from two large prospective cohort studies support the notion that obesity indexes, particularly CVAI, are significantly associated with the risk of CKD across diverse ethnic groups.